Uso de um sistema que contribui para a admissão contínua do comburente em um gaseificador de biomassa - Silva, Jandemarques Alexandre Soares da (2019)
The main goal of this research is to investigate the effects of an Ash Remover mechanism on a system formed by a biomass gasifier and a genset with a Diesel engine converted into an Otto cycle. The gasifier was designed to power a dual (poor gas / diesel) engine, with a maximum power electric generation of 20 kW. To operate the same engine only with poor gas, without harming its capacity to generate electric power, required many modifications. It was observed that the increase in the level of ashes produced by the gasifier, as a result of the increase in the electric power produced, was a natural event. When these ashes accumulates on the grate of the gasifier, there was a discontinuity in gasification. To solve this problem, a mechanic system that can allow the passage of gases and therefore the improvement of oxygenation has been installed. The system is manually operated whenever required, which in general occurs when the power of the genset is being increased. This work aims to evaluate the influence of such a system, on the performance of the gasifier/genset system. In order to evaluate the extent of possible interferences of the new apparatus in the system's own operation, a comparison was made between data from this work and data obtained from Luna (2018), using the same gasifier, but without Ash Remover Mechanism. In a second experiment, biomass was used with different specific mass, moisture content and calorific value. The specific consumption of the poor gas as a function of the generated power varied between 1.2 and 3.6%. In the case of the gasifier, it was seen that the efficiency, depending on the power, remained between 75 and 82%. The efficiency of the genset, in terms of the generated power, varied between 11 and 23%. The efficiency of the system formed by the gasifier / genset was almost linear as a function of the generated power and ranged between 8 and 19%. Most significantly, the curves plotted using the data of the present work, in several situations, bear great similarity both in their aspects and in their value distribution, with other in a related work. The use of the Ash Remover did not impair the prediction of the conventional behavior, of the fixed bed co-current open top gasifier, nor of the gasifier system / genset, equipped with equal apparatus. There is also the certainty that the use of the Ash Remover will be useful to guarantee continuous operation of the gasifier, since it can avoid the buffering of its grill.